Commensal bacteria contribute to the growth of multidrug-resistant Avibacterium paragallinarum in chickens - Zhu, Jiajia; Chen, Yunsheng; Wu, Yifan; Wang, Yongqiang; Zhu, Kui (Frontiers in Microbiology, 2022)
Avibacterium paragallinarum-associated infectious coryza (IC) is important threat in commercial poultry. Previous studies about the characteristics of A. paragallinarum are succeed in revealing the course of IC disease, but whether and how resident microbes contribute to the infection remain unclear. To understand the role of commensal bacteria, we isolated 467 commensal bacteria, including 38 A. paragallinarum, from the respiratory tract of IC chicken. The predominant commensal isolates were Gram-positive bacteria belonging to Staphylococcus spp. (33.19%, 155/467), Enterococcus spp. (16.49%, 77/467), and Bacillus spp. (16.27%, 76/467). These isolates were closely correlated with the survival of A. paragallinarum. We examined and found that commensal bacteria aggravate A. paragallinarum associated infections because certain commensal species (28.57%, 12/42) exhibited hemolysis and promoted the growth of A. paragallinarum in vitro. Notably, A. paragallinarum showed high resistance to routine antibiotics such as erythromycin (84.21%, 32/38), tetracycline (73.68%, 28/38) and carried diverse mobile resistance gene clusters. Overall, commensal bacteria, especially for Gram-positive commensals, facilitating the survival of multidrug-resistant A. paragallinarum exacerbate the infections, suggesting that novel strategies may diminish A. paragallinarum-associated infections by modulating the population dynamics of commensal bacteria.